Taurine inhibits Streptococcus uberis-induced NADPH oxidase-dependent neutrophil extracellular traps via TAK1/MAPK signaling pathways - Li, Ming; Gao, Yabing; Wang, Zhenglei; Wu, Binfeng; Zhang, Jinqiu; Xu, Yuanyuan; Han, Xiangan; Phouthapane, Vanhnaseng; Miao, Jinfeng (Frontiers in Immunology, 2022)
Neutrophil extracellular traps (NETs) are produced by neutrophil activation and usually have both anti-infective and pro-damage effects. Streptococcus uberis (S. uberis), one of the common causative organisms of mastitis, can lead to the production of NETs. Taurine, a free amino acid abundant in the organism, has been shown to have immunomodulatory effects. In this study, we investigated the molecular mechanisms of S. uberis-induced NETs formation and the regulatory role of taurine. The results showed that NETs had a disruptive effect on mammary epithelial cells and barriers, but do not significantly inhibit the proliferation of S. uberis. S. uberis induced NADPH oxidase-dependent NETs. TLR2-mediated activation of the MAPK signalling pathway was involved in this process. Taurine could inhibit the activation of MAPK signalling pathway and NADPH oxidase by modulating the activity of TAK1, thereby inhibiting the production of ROS and NETs. The effects of taurine on NADPH oxidase and NETs in S. uberis infection were also demonstrated in vivo. These results suggest that taurine can protect mammary epithelial cells and barriers from damage by reducing S. uberis-induced NETs. These data provide new insights and strategies for the prevention and control of mastitis in dairy cows.